A’tariq elaa Ala’rabia (The Arabic route) - Shreydeh, Mohammad (Dirasat: Human and Social Sciences, 2021)
A’tariq elaa Ala’rabia (The Arabic route) teaching curriculum is considered to be one of those strategies in the Arab and worldwide countries. It becomes a required method to teach Arabic for those who are willing to learn Arab language by natives or non-natives. As a result, this paper investigates the critical and the analytical parts of the this teaching curricula. It also aims to participate in constructing an extensive and comprehensive editions to teach Arabic language for those who are interested in learning Arabic specially the non-native speakers. This curricula was constructed as standard Arabic. The extensive Islamic Arabic texts and exercises are the main elements of this curricula. This study concludes that this curricula’s serial chain of books were constructed without an intensive knowledge of Arabic language. The academic linguistic part of was not discussed. Teaching a second language within this curricula was randomly built without taking in mind the step by step teaching process. The varieties of teaching strategies were not involved in these books series editions. Targeting a specific stream in the teaching process based on the religious aspect to teach a specific purpose was not thoroughly captured within these curricula. Finally, the absence of the listening and the speaking skills in these series’ editions gave the instructors the abilities to include different exercises unrelated to these editions.